Development and application of technical and economic strategies in upgrading heavy oil: the case of Iran / Nooshin Jabbari - Nooshin, Jabbari (2015)
Nowadays, due to the increasing demand for energy at an alarming rate, the alternative resources of energy are being explored to compensate the depleting conventional energy resources. One such alternative, if the upgrading processes are effectively managed, could be heavy crude oil. Iran is endowed with large resources of both conventional and unconventional Oil. However Due to the decrease in the conventional resources in Iran, the National Iranian Oil Company (NIOC) has been compelled to resort to the unconventional oil resources. However, the transition to heavier and sourer oil resources results in some technical, economic and environmental challenges for the downstream refining industry in Iran. These challenges require investing in new refinery technologies or/and a better crude feedstock to improve the quality of the downstream products. The best approach to curb major modifications for the current refineries is to upgrade heavy oil prior to its entrance to the refineries. Carrying out this treatment under optimum reaction conditions would be economically attractive to Iranian National Oil Company. This thesis discusses the development and application of technical and economical strategies to achieve an optimum solution for upgrading SOROOSH heavy oil. the first step was, to develop an experimental study based on the three most important variables for the hydro-treatment process and apply the ANN (Artificial Neural Network) system to predict the results. We identified a set of possible conditions to achieve the required feed specification for refineries in Iran i.e. sulphur and metals less than 1.6 %wt. and 100wppm respectively. In the second step, based on the objective model, the Nonlinear Programming (NLP) models for processing conditions were carried out which included several types of logic models to demonstrate the combination of three main variables, HSD/ HDM and utilities. Using MATLAB and SIMULINK software to simulate systematic models, the possible conditions (Temperature, Pressure and Liquid Hourly Space Velocity (LHSV)) for the desired HDS and HDM in the upgrading process of SOROOSH heavy oil were determined. Finally, all the economical functions and the parameters were fed to the indigenous software developed at Amirkabir University of Technology (AUT). To estimate the best conditions from an economical point of view for a 50,000 BPSD from SOROOSH crude oil. The results obtained from the simulation and the economic analysis; revealed suitable commercialization conditions under which an effective pathway to upgrade SOROOSH heavy oil, could potentially be provided with less capital cost. This thesis has proven the practicality of the proposed model as an efficient tool for planning the upgrading of SOROOSH’s heavy oil process from the technical and economical points of view and could open new markets for Iran and as a result increase the national revenue.